Transition from Simple V-V to V-A and Hybrid ECMO Configurations in COVID-19 ARDS - Piotr Suwalski; Jakub Staromłyński; Jakub Brączkowski; Maciej Bartczak; Silvia Mariani; Dominik Drobiński; Konstanty Szułdrzyński; Radosław Smoczyński; Marzena Franczyk; Wojciech Sarnowski; Agnieszka Gajewska; Anna Witkowska; et al. (Membranes, 2021)
In SARS-CoV-2 patients with severe acute respiratory distress syndrome (ARDS), Veno-Venous Extracorporeal Membrane Oxygenation (V-V ECMO) was shown to provide valuable treatment with reasonable survival in large multi-centre investigations. However, in some patients, conversion to modified ECMO support forms may be needed. In this single-centre retrospective registry, all consecutive patients receiving V-V ECMO between 1 March 2020 to 1 May 2021 were included and analysed. The patient cohort was divided into two groups: those who remained on V-V ECMO and those who required conversion to other modalities. Seventy-eight patients were included, with fourteen cases (18%) requiring conversions to veno-arterial (V-A) or hybrid ECMO. The reasons for the ECMO mode configuration change were inadequate drainage (35.7%), inadequate perfusion (14.3%), myocardial infarction (7.1%), hypovolemic shock (14.3%), cardiogenic shock (14.3%) and septic shock (7.1%). In multivariable analysis, the use of dobutamine (p = 0.007) and a shorter ICU duration (p = 0.047) predicted the conversion. The 30-day mortality was higher in converted patients (log-rank p = 0.029). Overall, only 19 patients (24.4%) survived to discharge or lung transplantation. Adverse events were more common after conversion and included renal, cardiovascular and ECMO-circuit complications. Conversion itself was not associated with mortality in the multivariable analysis. In conclusion, as many as 18% of patients undergoing V-V ECMO for COVID-19 ARDS may require conversion to advanced ECMO support.